2003
DOI: 10.1074/jbc.m302997200
|View full text |Cite
|
Sign up to set email alerts
|

The c-Jun N-terminal Kinase 1 Activity Is Differentially Regulated by Specific Mechanisms during Apoptosis

Abstract: We show here that JNK1 activity is rapidly up-regulated and prolonged by specific mechanisms during apoptosis induced by paclitaxel-or ginsenoside-Rh2 in SK-HEP-1 cells. The early phase of JNK1 activation is prevented in cells expressing the dominant negative SEK1 mutant, although this JNK1 perturbation does not prevent apoptotic cell death. The later phase of JNK1 activation, which is temporally coincided with caspasedependent cleavage of JNK1-associated p21 WAF1/CIP1 , is efficiently prevented by expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 35 publications
3
37
1
Order By: Relevance
“…These results suggest that glucose deprivation and CDDP may induce apoptosis, at least partially, through the activation of JNK/SAPK and that the overexpression of ASNS may inhibit apoptosis through the suppression of this JNK/SAPK activation. Unlike our results, several reports showed that 5-FU and other anticancer drugs also induced apoptosis through the activation of JNK/SAPK (31)(32)(33)(34). Contrastingly, the genetic removal of SEK-1, an immediate upstream activator kinase of JNK, promoted apoptosis of hepatocytes and T cells (35,36), which proposes that JNK has a dual role in cell survival.…”
Section: Discussioncontrasting
confidence: 96%
“…These results suggest that glucose deprivation and CDDP may induce apoptosis, at least partially, through the activation of JNK/SAPK and that the overexpression of ASNS may inhibit apoptosis through the suppression of this JNK/SAPK activation. Unlike our results, several reports showed that 5-FU and other anticancer drugs also induced apoptosis through the activation of JNK/SAPK (31)(32)(33)(34). Contrastingly, the genetic removal of SEK-1, an immediate upstream activator kinase of JNK, promoted apoptosis of hepatocytes and T cells (35,36), which proposes that JNK has a dual role in cell survival.…”
Section: Discussioncontrasting
confidence: 96%
“…The JNK pathway played a major role in the apoptotic effect of PKCyNuc because inhibition of JNK significantly decreased the apoptotic effect of the PKCy-Nuc. JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53).…”
Section: Discussionmentioning
confidence: 93%
“…(Fig. 6), and both have been implicated in mediating apoptosis in response to paclitaxel treatment (28,29,38,39). We have reported previously that BRCA1 sensitizes breast cancer cells to paclitaxelinduced apoptosis (21).…”
Section: Discussionmentioning
confidence: 93%